Transition metal complexes with a new tridentate ligand, 5-[6-(5-mercapto-1,3,4-oxadiazol-2-yl)pyridin-2-yl]-1,3,4-oxadiazole-2-thiol - KALAGOUDA GUDASI; MANJULA PATIL; RAMESH VADAVI; RASHMI SHENOY; SIDDAPPA PATIL (Journal of the Serbian Chemical Society, 2007)
A new ligand 5-[6-(5-mercapto-1,3,4-oxadiazol-2-yl)pyridin-2-yl]-1,3,4-oxadiazole-2-thiol (L) and its Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) complexes were synthesized. The authenticity of the ligand and its transition metal complexes were established by elemental analyses, conductance and magnetic susceptibility measurements, as well as spectroscopic (IR, 1H- and 13C-NMR, electronic, mass, ESR) and thermal studies. The IR and 1H-NMR spectral studies revealed the existence of the ligand in the thiol form in the solid state, whereas in the thione form in the dissolved state. The magnetic and electronic spectral studies suggest an octahedral geometry for all the complexes. The ligand acts as a tridentate ligand coordinating through the pyridine nitrogen and the nitrogen atoms (N-3' and N-3'') of the two oxadiazole rings. Antimicrobial screening of the ligand and its metal complexes were determined against the bacteria Escherichia coli and Bacillus cirroflagellosus, as well as against the fungi, Aspergillus niger and Candida albicans.